The efficacy of meditation on insula dysfunction in patients with chronic schizophrenia - Kong, Di; Zou, Shoukang; Huang, Yanqing; Li, Zezhi; Yang, Mi; Cui, Donghong (Frontiers in Psychiatry, 2025)
ObjectivesMeditation combined with antipsychotic medication can effectively improve the clinical symptoms and prognosis of patients with schizophrenia, but its underlying neural circuit mechanism is not clear. Many previous studies have shown that the symptoms of schizophrenia are related to dysfunction of the insula. We aimed to explore the neural circuitry mechanisms associated with insular dynamic functional connectivity in the treatment of schizophrenia with meditation combined with antipsychotics in a prospective controlled study.Methods30 chronic schizophrenia patients were accepted meditation + antipsychotic drug intervention for 8 months. At baseline, 29 age-matched normal healthy controls were used to identify the differential brain regions of dynamic functional connectivity between the insula subregions and the whole brain in the schizophrenia patient group. PANSS scale scores, RBANS scale scores and MRI data were collected at baseline, third month, and eighth month in the schizophrenia group, MRI data was collected at baseline in the healthy control group, then dynamic functional connectivity analysis of the whole brain was conducted using the six subregions of the insula(the left ventral anterior insula (L-vAI), right ventral anterior insula (R-vAI), left dorsal anterior insula (L-dAI), right dorsal anterior insula (R-dAI), left posterior insula (L-PI), and right posterior insula (R-PI)) as seed. Identify which dynamic functional connections in the differential brain regions were improved after meditation intervention at third and eighth month compared with baseline.ResultsAt baseline, global functional connectivity was significantly lower in the meditation group than in the healthy control group in the left orbital inferior frontal gyrus, right orbital inferior frontal gyrus, medial and paracingulate gyri, right hippocampus, and left auxiliary motor area. At the third and eighth month, schizophrenia patients in the meditation group showed significant improvement of functional connectivity between L-dAI、L-PI and right orbital part of inferior frontal gyrus compared with baseline. Although the PANSS scale scores were significant improvement in the meditation group at the third and eighth month than baseline, there was no significant difference in the RBANS scale scores.ConclusionLong-term treatment with meditation can improve the overall psychiatric symptoms of patients with schizophrenia and the abnormal dynamic functional association of the insula, which provides a clinical and neuroimaging basis for the widespread application of meditation in the treatment of schizophrenia.